Influence of different small-sided game formats on physical and physiological demands and physical performance in young soccer players - Castillo, D.; Rodríguez-Fernández, A.; Nakamura, F. Y.; Sanchez-Sanchez, J.; Ramirez-Campillo, R.; Yanci, J.; Zubillaga, A.; Raya-González, J. (The Journal of Strength and Conditioning Research, 2021)
The aim of this study was to quantify the acute impact of bout duration and individual interaction space on physical and physiological demands and on physical performance. Ten young male soccer players (age: 14.8 ± 0.6 years) from the same team playing in the National U-16 Division participated. Physical (total distance [TD]; distance covered at different speeds; and maximum velocity [Velmax]) and physiological (peak [HRpeak] and mean [HRmean] heart rate) parameters were collected for every bout during each small-sided game (SSG) format. Moreover, the effects of SSGs on horizontal jump (HJ) and 30-m sprint performances were evaluated. The SSG formats were composed of 6 players a side (including goalkeepers) and included 4 repetitions of 6 minutes in a space of 100 m2 (SSG1) or 200 m2 (SSG2) and 6 repetitions of 4 minutes in 100 m2 (SSG3) or 200 m2 (SSG4). The TD, the distance covered at different speeds, and Velmax were greater (p < 0.01, effect size [ES] = 1.25-5.95, large) in SSG2 and SSG4 than SSG1 and SSG3, respectively. Furthermore, the HRmean and HRpeak were lower (p < 0.05, ES = 1.53-2.23, large) during SSG3 than other SSGs. In addition, while a significant (p < 0.05, ES = 0.70-2.04, moderate to large) increase in SPR30 time in SSG1 and SSG3 was observed, HJ performance was not affected (p > 0.05, ES = 0.03-0.54, trivial to moderate) by any SSG format. These findings suggest increasing pitch size to induce greater physical demands and to use SSGs with smaller pitch size, and independently of the bout duration, to induce neuromuscular fatigue.